2009
DOI: 10.3852/08-163
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the parnafungins, antifungal metabolites that inhibit mRNA polyadenylation, from theFusarium larvarumcomplex and other Hypocrealean fungi

Abstract: Evaluation of fungal fermentation extracts with whole cell Candida albicans activity resulted in the identification of a novel class of isoxazolidinone-containing metabolites named parnafungins. Chemical-genetic profiling with the C. albicans fitness test identified the biochemical target as inhibition of polyadenosine polymerase, a component of the mRNA cleavage and polyadenylation complex. Parnafungins were discovered from fermentation extracts of fungi resembling F. larvarum isolated from plants, plant litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…Therefore, metabolite profiling and chemical classification may be used as support for phenotypic species recognition in Phomopsis and closely related Diaporthales. In addition, chemical characterization combined with phylogenetic analysis can be used as tools for the screening of closely related taxa and dereplication of crude extracts derived from large collections of samples (Larsen et al 2005;Bills et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, metabolite profiling and chemical classification may be used as support for phenotypic species recognition in Phomopsis and closely related Diaporthales. In addition, chemical characterization combined with phylogenetic analysis can be used as tools for the screening of closely related taxa and dereplication of crude extracts derived from large collections of samples (Larsen et al 2005;Bills et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Stadler et al (2010) showed that ITS-based clades within the genus Daldinia correspond with the production of "signature" metabolites, such as eutypine methyl ether. Bills et al (2009) used parnafungin biosynthesis as a valuable chemotaxonomic marker to track lineages within the Fusarium larvarum species complex. The genus Fusarium also ranks among well-surveyed fungi due to its capacity to synthesize trichothecene and zearalenone mycotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, more type material from the Fusarium -like clade could be included compared to the ITS-RPB2 combined tree, since all reference strains from Gräfenhan et al [1] had been sequenced for RPB2, but not all of them had been sequenced for ITS. A second tree was constructed by using type material published by Bills et al [5] from the " Fusarium " larvarum complex and the " Fusarium " merismoides complex, of which the members were respectively moved to Microcera and Fusicolla by Gräfenhan et al [1]. The ITS, LSU, and BT reference sequences were used, excluding one ambiguously aligned region for the BT gene marker and using the Viridispora alata CBS 421.88 strain from Bills et al [5] as outgroup.…”
Section: Methodsmentioning
confidence: 99%
“…They often occur as saprophytes in the soil, on trees or other fungi, and in aquatic environments [12]. In contrast to the well-studied species diversity of Fusarium sensu Gräfenhan et al [1], they have not been reported as plant pathogens or opportunistic human pathogens and only a few have been described to produce mycotoxins [25]. Members of the Fusarium -like clade have therefore been largely neglected for a long period of time.…”
mentioning
confidence: 99%